Gambaran Kadar Ureum dan Nilai Estimated Glomerular Filtration Rate (eGFR) pada Pasien Diabetes Melitus Tipe 2 di RSUD ODSK Provinsi Sulawesi Utara - Samuel Lucman; Youla Annatje Assa; Stefana Helena Margaretha Kaligis (Pusat riset dan Inovasi Nasional, 2026)
Type 2 Diabetes Mellitus (T2DM) is a global health problem with continuously increasing prevalence, covering the majority of diabetes cases worldwide. Persistent hyperglycemia in T2DM progressively damages the kidneys. Early assessment of kidney function, especially through the examination of urea levels and estimated glomerular filtration rate (eGFR) values, is important to predict CKD prognosis and guide therapeutic intervention. To discover the profile of urea levels and eGFR values in Type 2 Diabetes Mellitus patients at ODSK Hospital, North Sulawesi Province. This study is a descriptive quantitative observational study with a cross-sectional design, conducted retrospectively using secondary data from the medical records of Type 2 Diabetes Mellitus patients at ODSK Hospital, North Sulawesi Province during the period February 2024–August 2025 who met the inclusion criteria. From a total sample of 658 Type 2 Diabetes Mellitus patients, the majority of patients had high urea levels (53.3%). Based on sex, the proportion of high urea levels in males (57.2%) was higher compared to females (50.5%). Meanwhile, the distribution of eGFR values showed that the G1 category was the most frequent (23.9%). However, the majority of other patients (75.1%) were already in categories G2 to G5, which indicates a decrease in kidney function. This decrease in kidney function was slightly more detected in male patients (76.1%) compared to female patients (74.4%). Type 2 Diabetes Mellitus patients at ODSK Hospital, North Sulawesi Province, have high urea levels and the majority have decreased eGFR values.